Assessment of the influence of various tree species and their parameters on the behaviour of wind flows in urban environments (on the example of the RUDN University campus, Moscow). Issue 1 (December 2020) - Bukin, S S; Fadeeva, I A; Yaroslavtsev, A M; Konstantinov, P I; Vasenev, V I; Valentini, R
Abstract: Urban environments are constantly growing, as a result of which natural surface covers are replaced by artificial materials. These changes have a strong impact on the wind fields in these urban environments, changing speeds and directions of wind flows. The aim of this study is to assess the effects of various tree parameters on the behaviour of wind flows in an urban environment. The EnviMet software package is used to model wind fields. The study is conducted in the city of Moscow on the RUDN University campus. Ten different kinds of trees are identified with characteristics such as tree height, crown width, trunk height, and the LAD (Leaf Area Density) index. For these species, a similar analysis is carried out to assess their impact on the wind field. The height of the trunk has a significant effect on the wind field at the pedestrian level; depending on the parameter, the wind speed and the area of wind gusts increase. Large crowns create a protective barrier, reducing wind activity. At the same time, a high LAD index creates low wind permeability, as a result of which the wind flows are refracted, and dangerous zones arise. On the other hand, a high LAD index reduces the area of wind gusts.